Ensuring Public Order during the Court Hearings in the Context of Reforming the Judicial System of Ukraine - Dzhafarova, M.; Ivanova, H.; Zahorodniuk, S.; Zaiets, U. (My University, 2020)
The relevance of the issue raised in the article is due to the fact that one of the key aspects of reforming the judicial system in Ukraine, which must meet European standards, is to ensure public order during the court hearing. In this regard, the subject matter of the article is the world-tested methods and ways of ensuring public order during the court hearing. While writing the article the authors have used the following methods: formal and legal, analytical, system analysis, system and structural. The problems that currently exist and are in the way of effective development of the national judicial system of Ukraine have been analyzed. While analyzing the most problematic and relevant issues of ensuring public order in courts the authors have emphasized on the intensification of tendencies to strengthen the security of the subjects participating in the court hearing. At the same time, it has been stated that there is the spread of the policy of many states for increasing the level of democratization of the judicial process, in particular by granting wider rights and freedoms to all its participants. Based on the successful experience of foreign countries, the authors have suggested the ways to improve the judicial process in Ukraine in the whole and not just to ensure public order during the court hearing. Special attention has been paid to the Judicial Protection Service. It has been determined that the improvement of the national legislation of Ukraine on ensuring public order during the court hearing should take into account both national traditions of judicial proceedings and European standards. At the same time, the implementation of international standards in these areas should be systematic and comprehensive. In this regard, it is necessary to form a single concept in this area. The conclusions have offered three main interrelated stages of improvement of the legislation of Ukraine in terms of ensuring public order during the court hearing.
Dzhafarova M. Ensuring Public Order during the Court Hearings in the Context of Reforming the Judicial System of Ukraine / Dzhafarova, H. Zahorodniuk, U. Zaiets // Amazonia Investiga. – 2020. – Vol. 9, Issue 32. – С. 10-17.
Keywords: court hearing; public order; court process; protection of public order; protection of subjects; ensuring public order; innovative methods; security of persons; quality process